2019
DOI: 10.1002/dmrr.3230
|View full text |Cite
|
Sign up to set email alerts
|

Weighting approaches for a genetic risk score and an oxidative stress score for predicting the incidence of obesity

Abstract: Background:We aimed to predict the incidence of obesity in a Korean population using a genetic risk score (GRS) constructed with obesity-related single nucleotide polymorphisms (SNPs) along with an oxidative stress score (OSS). Methods:A total of 9460 Korean subjects and 356 974 SNPs were included. The GRS was constructed using three significant obesity-related SNP loci, and the OSS was calculated with three reliable oxidative stress biomarkers. Results:The GRS showed a more significant association with increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…OxLDL is well known for its key pathogenic role in formation and progression of atherosclerotic plaque by promoting infiltration of macrophages followed by their activation and inflammatory cytokine release [63]. Moreover, oxLDL was found to be linked to cardiovascular disease [64], obesity [65], diabetes mellitus [66] and metabolic syndrome [67]. In the pediatric population oxLDL was found to correlate with waist-hip ratio (WHR) and its concentration was significantly higher in obese/overweight children in comparison to lean patients [68].…”
Section: Oxidized Low-density Lipoproteinmentioning
confidence: 99%
“…OxLDL is well known for its key pathogenic role in formation and progression of atherosclerotic plaque by promoting infiltration of macrophages followed by their activation and inflammatory cytokine release [63]. Moreover, oxLDL was found to be linked to cardiovascular disease [64], obesity [65], diabetes mellitus [66] and metabolic syndrome [67]. In the pediatric population oxLDL was found to correlate with waist-hip ratio (WHR) and its concentration was significantly higher in obese/overweight children in comparison to lean patients [68].…”
Section: Oxidized Low-density Lipoproteinmentioning
confidence: 99%
“…Therefore, in establishing a predictive model for prediabetes and T2DM, the OSS model, whose AUC was 0.680, showed better predictive performance than the BMI model in prediabetes and T2DM. In addition, Park et al [28] have previously proposed an OSS that solely used three intrinsic biomarkers of oxidative stress, namely MDA, ox-LDL, and 8-epi-PGF 2α , and showed that a higher OSS was associated with a higher risk of obesity. Therefore, in this study, the OSS using biomarkers can accurately reflect the internal unmodifiable factors of oxidative stress and can act as an indicator to predict the incidence of prediabetes and T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to our result, some studies that explored a global oxidative stress index (Oxidative-INDEX) did not reach beyond the good prediction level. Park et al [50] created an oxidative stress score consisting of MDA, oxidized low-density lipoprotein, and 8-epi-prostaglandin F2α. The AUC value was 0.75 when combined with single nucleotide polymorphisms to predict obesity in the Korean population.…”
Section: Discussionmentioning
confidence: 99%